Wavefront reversal technique for self-referencing collimation testing - Hii, K.U.; Kwek, K.H. (Optical Society of America, 2010)
We present a wavefront reversal technique to produce a dual-field fringe pattern for self-referencing collimation testing in wedge-plate lateral-shear interferometry. The method requires only a suitably placed cubic beam splitter to produce two replicas of the fringe field formed by the wedge-plate lateral-shear interferometer. One of the replicas has a fringe pattern that is the reverse of the other. With these two fringe fields, the collimation testing has a built-in reference, and the detection sensitivity is twice that of a single-wedge-plate technique. (C) 2010 Optical Society of America